The influence of creativity and learning motivation on entrepreneurial intentions of fisheries vocational high school students - Priyono Priyono; Achmad Imam Agung; I Gusti Putu Asto Buditjahjanto; Lilik Anifah; Tomi Agfianto (Jurnal Pendidikan Vokasi, 2024)
The fisheries department is one of the expertise programs in Vocational High Schools (VHS). Learning motivation towards the entrepreneurial intention of VHS students majoring in fisheries is still low. This is supported by the fact that some students do not know the relationship between entrepreneurial intentions and learning motivation, which can arouse students' intentions for entrepreneurship. Therefore, this research aims to see the effect of creativity and learning motivation on the entrepreneurial intentions of VHS students majoring in fisheries. This research is ex post facto research with a quantitative approach because the data is generated in the form of numbers and analyzed based on statistical analysis. The sample in this research was 100 students, and the sampling technique used was purposive sampling. The data analysis technique used is multiple regression analysis. The results of this research explain that creativity has an influence on entrepreneurial intentions, and learning motivation has an influence on entrepreneurial intentions. This is evidenced through the results of the t-test where the sig value obtained is 0.003, whose value is much smaller than 0.05 (0.001 < 0.05) and the t-count is greater than the t-table (2.614 > 1.984), so it can be said that creativity has an influence on entrepreneurial intention, as well as the learning motivation variable where the t-count value is greater than the t-table (2.679 > 1.984). This research contributes to the literature by providing insight into the role of creativity and learning motivation in shaping student entrepreneurial intentions, which can inform the development of entrepreneurship education programs and policies.